Malignant masquerade: A case report of urachal malakoplakia disguised as urachal tumor - Imad Boualaoui; Adam El Aboudi; Mohammed Ali Mikou; Hamza El Abidi; Salim Ouskri; Saad Mesbahi; Ahmed Ibrahimi; El Sayegh Hachem; Nouini Yassine (Urology Case Reports)
Malakoplakia is a rare inflammatory disease that predominantly affects the genitourinary tract, with the urinary bladder being the most commonly involved site. Although its exact pathogenesis remains unknown, it is well-established that the condition is associated with chronic urinary tract infections and immunosuppression. Its presentation often poses a significant diagnostic challenge, as it can closely mimic malignancy. We report a case of a 55-year-old female who presented with lower urinary tract symptom with a palpable hypogastric mass, imaging suspected urachal tumor. A partial cystectomy was performed, which histology confirmed the diagnostic of Urachal Malakoplakia.